Resettlements issues in Sri Lanka; with special reference to ‘Yan Oya’ project - SANJEEWANI MAHESHIKA MALWATTA; WASANTHA SUBASINGHE (Journal of Advanced Research in Social Sciences and Humanities, 2021)
Aim: This research aims to pinpoint the specific factors that need to be considered to lessen the negative effects of socioeconomic factors during the planning stages of a resettlement project. Methodology: The quantitative cross-sectional study used a positivistic methodology. Under the survey design, raw data was gathered via structured questionnaires and semi-structured interviews. 51 households were drawn from Displaced Person due to the ’Yan Oya’ development project using a simple random probability sample method. Findings: The original lands were flooded by the reservoir created by the Yan Oya project. The mud farming and chena cultivation provided for them in the early settlement were abandoned. There is currently no land available for chena cultivation, but land in the resettlement area has been fairly distributed. This forced resettlement resulted in several adverse outcomes, including increased costs associated with day-to-day living, separation from loved ones, fraying socialties, and isolation from neighbors. The community infrastructure found crumbled. Implications/Novel Contribution: The proposed relocation to this area comes straight from the government. However, the benefits and the infrastructure offered to them could be better thought out. There are a lot of unmet social, economic, and emotional requirements. Compared to the positive effects, the negative ones of this resettlement are enormous. They require more help in financials, technical know-how, land, market facilities, new job opportunities, and training for jobs in the information and communications technology (ICT), electric, mechanic, and automobile industries. Training, financial aid, and other resources should be available to unemployed women interested in starting their own businesses.